THE Histori Of Child Death With Women Fertility Of Childbearing Age In Bengkulu Province: Fertility - Bintang Agustina Pratiwi; Nopia Wati; Oktarianita ok; Wulan Angraini; Mugia Bayu Raharja (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Background: Fertility in Bengkulu province shows 2.3, although it is lower than the national figure, this figure shows that there are still many women of childbearing age who have more than two children. Meanwhile, the neonatal mortality rate is increasing . The purpose of this study was to determine the relationship between the history of child mortality and the fertility of women of childbearing age. Method: Quantitative research with a cross sectional design. The data used is secondary data sourced from the Indonesia Demographic and Health Survey (IDHS) 2017, focusing on the childbearing age with a total sample of 274 people meeting the criteria. The location chosen is Bengkulu province. Data analysis was carried out by univariate and bivariate (chi square).Results: most of the respondents had 2 children (65.6%) and had no history of child mortality (90.2%). There is a relationship between Child Mortality History and fertility of urban age women. Conclusion: Age fertility in suburban Bengkulu province affects the history of child mortality.